Analysis of Aluminum Sulfate Dosage on Water Quality Parameters in the Coagulation-Flocculation Process: Analisis Dosis Aluminium Sulfat terhadap Parameter Kualitas Air Pada Proses Koagulasi-Flokulasi - Fadhilah Labibah Nurjanah; Okik Hendriyanto Cahyonugroho; Rizka Novembrianto (Media Ilmiah Teknik Lingkungan (MITL), 2026)
This study aims to evaluate the performance of aluminum sulfate (alum) coagulant in river water, tofu waste, and batik waste with varying doses on the effectiveness of the coagulation-flocculation process. The method used was a jar test on 1000 mL of water samples, including coagulation for 1 minute at 120 rpm, and flocculation for 20 minutes at 40 rpm, and sedimentation for 15 minutes. The variations in alum doses used were 150 mg/L, 200 mg/L, and 250 mg/L. The results showed that this process caused pH changes during treatment and was effective in reducing turbidity, TSS, and color although the optimum dose differed for each sample. In river water, the optimum dose of 150 mg/L resulted in 98.99% turbidity removal, 81.82% TSS removal, and 99.11% color removal. Meanwhile, for tofu waste, the optimum dose of 250 mg/L resulted in 86.67% turbidity removal, 98.66% TSS removal, and 96.16% color removal. Meanwhile, for batik waste, the optimum dose of 200 mg/L resulted in 97.89% turbidity removal, 95.76% TSS removal, and 91.61% color removal. This indicates that the coagulant dosage needs to be adjusted to the characteristics of each type of sample used.